English Foreign Language Students’ Strategies in Overcoming Speaking Problems - Ari Prasetyaningrum; Laila Wati; Zahratul Fikni (Universitas Hamzanwadi, 2020)
This study aimed at knowing students’ dominant problems in speaking and students’ strategies in overcoming their speaking problems. In this study the researcher used qualitative research. The subject of this study was the students’ of the second semester of physics education study program at Hamzanwadi University which consisted of 12 students’. Observation, interview and questionnaire were used for collecting data. The result of this study showed that students’ got the problems in speaking, the students’ dominant problems those were anxiety of speaking, unavailability environment and lack of vocabularies. In solving the students’ problem in speaking, the students’ used some strategies those were role-play, telling-story and games.